Competency construct model for critical reading in non-literary texts based on the framework of the Indonesian National Qualification (KKNI) - Rahayu, Dwi Hanti; Nurbaya, St. (Fakultas Bahasa, Seni, dan Budaya, Universitas Negeri Yogyakarta, 2022)
The ability to read is a language skill that is very important in supporting general academic abilities. Based on research, most study programs at higher education institutions do not include critical reading as a subject. For this reason, this study aims to produce a construct model of critical reading competencies in non-literary texts which is used as a guideline for evaluating learning outcomes (LO) in critical reading classes. The ptesent study is developmental research with the stages of preliminary study activities, literature studies, field analysis, and competency product development. The data source for the study is analysis of data needs to build critical reading competences. Results of the study show that there are five steps of activities carried out in critical reading, namely: 1) surveying the text, 2) understanding the contents of the text, 3) analyzing the text, 4) criticizing the text, and 5) evaluating and publishing. Step (1) determines the type of text to be criticized, identifing the identity and background of the author. Step (2) determines the theme of the text, shows the characteristics of the text, and states the main ideas of each paragraph. Step (3) identifies the structure of the text, states facts and opinions, determines the pattern of paragraph development, identifies relationships between main ideas and explanations, restates implied meanings, and understands the relevances of the relationships among text structures. Step (4) shows the discrepancy between the theme and the content, the description in each part of the text, the ideas in the paragraphs, the details of facts, and the author's arguments. Step (5) assesses the accuracy and suitability of the facts. The final stage is publication of results showing strengths and weaknesses of the text.Keywords: construct model, critical reading, non-literary text